Kesehatan Dan Keselamatan Kerja Pada Petugas Radiologi Di Instalasi Radiologi Rumah Sakit Pertamedika Banda Aceh - Pocut Zairiana Finzia; Alvin Sahri (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this research is to find out the health and safety of the radiologist and how to protect the radiologist in the radiology installation of the Pertamedika Hospital in Banda Aceh. This research is descriptive qualitative research. The result of this research shows that the application of the Hospital Health Management and Safety Management System (SMK3RS) to the staff needs to be applied to create a healthy, safe and calm work environment, so as to reduce the probability of work accidents. The health and safety of work is also very important in the installation of radiology